The influence of family health strategy on health indicators in the municipalities of Rio de Janeiro, Brazil - Magnago, Carinne; Pierantoni, Celia Regina; França, Tania; Garcia, Ana Cláudia; Ney, Márcia Silveira; Matsumoto, Karen (Online Brazilian Journal of Nursing, 2011)
ABSTRACT: This study examines the behavior of health indicators deployment of Family Health in the cities of Rio de Janeiro, Nova Iguaçu and Duque de Caxias. This is ecological study of time series of selected variables in the period 1998 to 2010. Data were collected at the websites of DATASUS and Department of Primary Care and later exported into a spreadsheet, tabulated and analyzed using inferential statistics with calculation of Pearson coefficient (r) and t test at a significance level of 5% (α = 0.05). There was a strong negative correlation with statistical significance between the evolution of family health and: number of deaths from infectious and parasitic diseases in Rio de Janeiro and Duque de Caxias; frequency of hospitalized children with diarrhea in Rio de Janeiro and Nova Iguaçu; and frequency of hospitalization for diabetes mellitus in Rio de Janeiro. It is concluded that the strategy of family health influence the behavior of health indicators for the cities studied, however, further research will be needed to investigate further the impact of family health in cities with high population density.